Promoting and Attracting Foreign Direct Investment - Elena Chirila Donciu (CES Working Papers, 2014)
FDI is an important element of the economic development of any country and its functioning on market principles. They have a great importance for strengthening the economy of countries in transition and their integration into the world's economy. The modernization of national economies occurs with FDI help, by implementing advanced technologies, know-how sites, the most powerful equipment and the new quality standards by switching to a higher type of growth. The purpose of this research is to identify of the policies to attract and promote FDI, adopted by host countries for foreign investors and are highlighted beneficial aspects of foreign investments flows on recipient economies. The research results show that policies aimed at ensuring access to foreign markets, those that are considering providing commercial facilities and last, but not least, policies focused on tax incentives are very important for foreign investors.
Keywords: E22; F43; P33; 330; Foreign direct investment; Economic growth